Comparing UK Tax Returns of Foreign Multinationals to Matched Domestic Firms - Bilicka, Katarzyna Anna (American Economic Review, 2019)
In this paper, I use confidential UK corporate tax returns data to explore whether there are systematic differences in the amount of taxable profits that multinational and domestic companies report. I find that the ratio of taxable profits to total assets reported by foreign multinational subsidiaries is one-half that of comparable domestic standalones. The majority of the difference is attributable to the fact that a higher proportion of foreign multinational subsidiaries report zero taxable profits. I document how the estimated difference is related to profit shifting and show that using accounting data leads to much smaller estimates of the difference. (JEL F23, H25, H32, L25)